Embodied Cognition, Kinaesthetic Knowledge, and Kinesic Imagination in Literature and Visual Arts - Bolens, Guillemette (Frontiers in Communication, 2022)
Embodied cognition, kinaesthetic knowledge, and kinesic imagination are central not only to acts of creation but also to the reception of artworks. This article substantiates this claim by focusing on sensorimotricity in art and literature, presenting two sets of analytical distinctions that pertain to dynamics in gesture and movement. The first set of distinctions—kinesis, kinaesthesia, kinetics, and kinematics—and the second set—timing, tempo, and momentum—are used to analyse literary descriptions and visual depictions of movements. The first set of distinctions is discussed in the first section of the article in relation to medieval drawings and literary excerpts from different historical periods (in works by Ovid, Shakespeare, and Proust). The second section focuses on visual arts and leads to an analysis of Bruegel’s _Fall of the Rebel Angels_, while the third section presents a kinesic analysis of the Apollo and Daphne episode in Ovid’s _Metamorphoses_. A heightened attention to the cognitive processing of kinesic features in acts of reception enhances the role and responsibility of readers and viewers in the ways in which they grasp the movement-based meanings formalized by artists of various cultures and historical periods.